Escolha de parceiros na adolescência - Hattori, Wallisen Tadashi (2009)
Mate choice is a component of sexual selection. Trying to understand the patterns of this process, several studies have emphasized the adaptive value of sexual differences and their influence on the assessment of the market value. The pattern for adults presented on the scientific literature, which is based on the preference for certain characteristics, shows that men search a partner who shows high value of fecundity and fertility, thus looking for partners with the ability of being pregnant and nursing their offspring. On the other hand, women look for partners with high socioeconomic status, which is strongly associated with the ability to protect and provide resources for them and their offspring. Surprisingly, there is few works that investigated the mate choice patterns during the beginning of the period of sexual differentiation on the morphological, physiological and behavioral traits. The aim of this study was to investigate mate choice patterns in adolescence in order to describe their preferences and contribute to the understanding of human reproductive behavior. Took part of this research 1,232 students from educational institutions of Natal, Brazil, and visitors to the Scientific, Technological and Cultural Fair UFRN. In the Experimental Study 1, we applied a questionnaire to evaluate the importance of certain characteristics, assessed the degree of romantic involvement and real and ideal partners age preference. In the Experimental Study 2, we did a survey of characteristics considered relevant and evaluate the importance of these characteristics in mate choice. The Experimental Study 3 brought an investigation of mate choice patterns based on self-assessment of adolescents, evaluating ideal partner for a short-term and long-term relationships and actual partner. We found that adolescents are motivated to live romantic experiences. We also observed a preference for partners of similar age to that described for adults. Finally, we found similarities and differences in the preferences for characteristics in real and ideal partners in relation to the adult pattern. In addition, we observed high similarity on the self-assessment and assessment of real and ideal partners. We suggest that in the mate choice, adolescents are similar to young adults in some aspects but not all. Our results show the relevance of the reproductive behavior investigation in this human developmental period and reinforce that further studies should contribute to the understanding of human behavior in terms of ontogenetic development and their evolutionary history.